2023
DOI: 10.3390/cancers15082377
|View full text |Cite
|
Sign up to set email alerts
|

Role for Neoadjuvant Systemic Therapy for Potentially Resectable Pancreatic Cancer

Abstract: Despite aggressive adjuvant management, a high percentage of patients who undergo appropriate surgical resection for pancreatic cancer will see their cancer recur and thus will not be cured. An important paradigm shift to achieve better outcomes has been therapy sequence, with neoadjuvant chemotherapy preceding surgery. Patients with a borderline resectable cancer, or patients with a resectable cancer but who have other high-risk features, are ideal candidates to consider for neoadjuvant chemotherapy. Among th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…In addition, they also showed that the resection rate and R0 resection rate were similar in patients who did and did not receive NAC-GS, although the rate of administration of AC was increased in the former group. Our results were in line with those of a previous meta-analysis in some respects [8] but different from those of the Prep-02/JSAP05 study, which showed a survival benefit of NAC-GS [25]. A recent meta-analysis also suggested that NAT is associated with a lower risk of development of lymph node metastasis, an improved R0 resection rate, and improved recurrence-free and overall survivals in patients with resectable disease [11].…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…In addition, they also showed that the resection rate and R0 resection rate were similar in patients who did and did not receive NAC-GS, although the rate of administration of AC was increased in the former group. Our results were in line with those of a previous meta-analysis in some respects [8] but different from those of the Prep-02/JSAP05 study, which showed a survival benefit of NAC-GS [25]. A recent meta-analysis also suggested that NAT is associated with a lower risk of development of lymph node metastasis, an improved R0 resection rate, and improved recurrence-free and overall survivals in patients with resectable disease [11].…”
Section: Discussionsupporting
confidence: 75%
“…The five-year overall survival rates were 20.5% in the test arm and 6.5% in the control arm [ 25 ]. However, the results of meta-analyses have been conflicting [ 8 , 11 ]. More recently, the effectiveness of modified FOLFIRINOX in a neoadjuvant setting has been examined [ 26 ].…”
Section: Evidence Of the Benefits Of Adjuvant/neoadjuvant Chemotherap...mentioning
confidence: 99%
See 2 more Smart Citations
“…According to a growing body of research, neoadjuvant chemotherapy is increasingly being used as a therapeutic option for patients with pancreatic cancer who may otherwise be candidates for surgery [ 7 ]. Conroy et al demonstrated that, despite having a greater prevalence of severe side effects, adjuvant treatment with a modified FOLFIRINOX regimen (leucovorin, 5-fluorouracil, irinotecan and oxaliplatin) resulted in considerably longer survival times than gemcitabine among patients with resected pancreatic cancer [ 8 ].…”
Section: Introductionmentioning
confidence: 99%